Predictive Factors for Access-Site Pain Chronicity after Percutaneous Coronary Intervention via Radial Artery Access. (17th November 2020) - Brogiene, Liuda; Baksyte, Giedre; Klimaite, Agne; Paliokas, Martynas; Macas, Andrius
Abstract : Objectives . The aim of this study is to assess the prevalence and predictive factors for developing chronic access-site (A-S) pain after percutaneous coronary intervention (PCI) via radial artery access. Methods . Data of selected patients ( n  = 161) who underwent elective PCI were collected prospectively and analysed in 2020. Verbal analogue scale was used to evaluate pain intensity after 12, 24, and 48 h and 3 months after PCI. The univariate logistic regression analysis was used. Results . Pain prevalence decreased from 29% straight after PCI and 54% two hours later to 3.7% following 3 months after procedure. The predictors for A-S pain chronicity are diabetes (OR = 5.77 95% CI (1.07–31.08), p = 0.041 ), hematoma (OR = 6.48, 95% CI (1.06–39.66), p = 0.043 ), A-S hand neuropathy (OR = 19.93 95% CI (1.27–312.32), p = 0.033 ), A-S pain immediately after PCI (OR = 14.60 95% CI (1.63–130.27), p = 0.016 ), after 12 h (OR = 17.2 95% CI (1.60–185.27), p = 0.019 ), 24 h (OR = 48 95% CI (4.87–487), p = 0.01 ), and 48 h (OR = 23.46 95% CI (3.81–144.17), p = 0.001 ), and pain intensity immediately after procedure (OR = 3.30 95% CI (1.65–6.60), p = 0.001 ), after 2 h (OR = 2.56 95% CI (1.15–5.73), p = 0.022 ), after 12 h (OR = 3.02 95% CI (1.70–5.39), p < 0.001 ), after 24 h (OR = 3.58 95% CI (1.90–6.74), p < 0.001 ), and after 48 h (OR = 2.89 95% CI (1.72–4.87), p < 0.001 ). Pain control was performed with Ketoprofen and Ibuprofen as most used NSAIDs. 10 mg of Morphine intravenously was the choice from strong opioids if necessary. Conclusions . The prevalence of chronic A-S pain is 3.7%. Main predictive factors for the A-S pain chronicity are diabetes, hematoma, and persistent pain and pain intensity during 48 h period after PCI.